Ability of people with post-stroke hemiplegia to self-administer FES-assisted hand therapy video games at home: An exploratory case series. (June 2019) - Fu, Michael J; Harley, Mary Y; Hisel, Terri; Busch, Robyn; Wilson, Richard; Chae, John; Knutson, Jayme S
Introduction: This article describes the development and initial clinical testing of an innovative home-based treatment for upper extremity hemiplegia that integrates contralaterally controlled functional electrical stimulation with hand therapy video games. Methods: We explored the ability of seven participants with moderate-to-severe hand impairment to self-administer 12 weeks of contralaterally controlled functional electrical stimulation video game therapy at home for 10 h/week and in-lab with a therapist for four h/week. Clinical suitability was assessed by device usage logs, qualitative surveys, and clinical motor and cognitive outcomes. Results: Three participants completed the study with > 95% compliance and four did not. Factors linked to incompletion included development of trigger finger in the non-paretic hand, acceptance of a new full-time job, residence relocation, and persistence of drowsiness from anti-spasticity medication. Those who completed the treatment perceived qualitative benefits and experienced gains in motor and cognitive outcomes. Conclusion: Individuals with moderate-to-severe chronic post-stroke upper extremity hemiplegia can self-administer contralaterally controlled functional electrical stimulation video game therapy for up to 90 min/day at home. We also identified social and physiological factors that may preclude its use for daily home treatment. Further studies are warranted and are in progress to estimate treatment effect and optimal dose of this intervention.